2012
DOI: 10.1007/s10461-012-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Female Condom Use and Interest Among Injection Drug-Using Female Sex Workers in Two Mexico–US Border Cities

Abstract: Little is known about female condom use among female sex workers who inject drugs (FSW-IDUs) in Northern Mexico, where HIV/STI prevalence is high. We examined the prevalence and correlates of female condom use and interest in female condom use among FSW-IDUs aged ≥18 years in Tijuana and Ciudad Juárez, Mexico enrolled in a behavioral intervention designed to reduce high-risk sexual and injection behaviors. Of 621 FSW-IDUs, 8 % reported ever using female condoms, and 67.2 % expressed interest in trying female c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Condom use is often seen as inappropriate in these non-paying partnerships (Maher et al, 2013; Richter et al, 2002). In entertainment and sex work contexts, condom use, or the suggestion of condom use has been associated with increased violence from clients (Stockman et al, 2012), in addition to intimate partners (Argento et al, 2014). The proportion of women in this study who experienced violence from non-paying partners is within the range reported in previous studies (Decker et al, 2014; Hong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Condom use is often seen as inappropriate in these non-paying partnerships (Maher et al, 2013; Richter et al, 2002). In entertainment and sex work contexts, condom use, or the suggestion of condom use has been associated with increased violence from clients (Stockman et al, 2012), in addition to intimate partners (Argento et al, 2014). The proportion of women in this study who experienced violence from non-paying partners is within the range reported in previous studies (Decker et al, 2014; Hong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar micro-social contexts exist surrounding condom use in intimate relationships, where protection is rarely used because of love, trust, and commitment (9; 11; 16; 38; 42••; 46). Condom use remains low in intimate relationships when compared to sex with casual and commercial partners (9; 14).…”
Section: Trust and Commitment In Intimate Relationships And Hiv Risksmentioning
confidence: 96%
“…1722 Although little is known regarding the specific factors that affect utilization of HIV-related services among street-based female sex workers in the U.S., 18 data from international studies indicate that stigma, discrimination, and denial of risk are particularly salient barriers to testing in many locations, along with lack of knowledge and access to HIV testing services. 19, 2326 …”
mentioning
confidence: 99%
“…14, 28, 29 International research on voluntary counseling and testing services for female sex workers has widely documented low uptake of HIV testing among this group, with approximately 20% to 50% reporting prior HIV testing. 19, 2326 Although data on HIV treatment utilization are even more limited, one recent study among female sex workers in Rwanda indicated that just 63% of the HIV infected were linked to care. 30 In the U.S., prior research in South Florida has documented an HIV prevalence of 25% among street-based African American female sex workers, 14 nearly half of whom were undiagnosed prior to the study due to low utilization of routine HIV testing services.…”
mentioning
confidence: 99%